A dimensão cultural das sementes tradicionais e a necessidade de proteção pelo sistema jurídico - Buriol, Fabiano (2015)
In the present dissertation is analyzed the need of protection of the traditional seed in reason to its wide use on several cultural manifestation. The theme was chosen according to the personal perception and history of life of the Master degree student, having his knowledge improved by bibliographic and legislative consultation as well as interviews. Starting with the studies of traditional people and communities as well the traditional seeds, as these groups are the main responsible by the preservation and insertion of the seeds in our lives, and the seeds play a fundamental role in cultural manifestations, mainly of the traditional people and communities, but also in the society in general. Is approached the cultural importance of nature and its presence in the formation of Brazilian cultural heritage, demonstrating that the traditional seeds deserve the same protection as other cultural assets. It is concluded then that these seeds are cultural goods indispensable to the preservation of cultural manifestations of the whole society, and therefore they should be protected by cultural heritage tutorship instruments.